2010
DOI: 10.1188/10.onf.711-717
|View full text |Cite
|
Sign up to set email alerts
|

Physical Access Barriers to Care for Diagnosis and Treatment of Breast Cancer Among Women With Mobility Impairments

Abstract: Objective-To explore the perceptions of breast cancer patients with mobility impairments of the physical accessibility of health care equipment and facilities Research Approach-One-to two-hour individual interviews, audiotaped Setting-Interviews in homes or workplaces or by telephoneParticipants-20 women with chronic mobility impairments who developed early-stage breast cancer before age 60; 3 recruited from oncologist panels and 17 from informal networks of disabled women nationwide Methodologic Approach-Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 15 publications
2
79
0
13
Order By: Relevance
“…12,15 Women with movement difficulties confront obvious barriers to mammography, when women cannot stand and facilities have not accommodated them through wheelchair accessible equipment, specialized mammography chairs, additional technician support, or other adaptations. 12,32 …”
Section: Discussionmentioning
confidence: 99%
“…12,15 Women with movement difficulties confront obvious barriers to mammography, when women cannot stand and facilities have not accommodated them through wheelchair accessible equipment, specialized mammography chairs, additional technician support, or other adaptations. 12,32 …”
Section: Discussionmentioning
confidence: 99%
“…36 These barriers might help explain broader findings about lower mammography use among women with physical disabilities. [6][7][8][9][10][11] Partnerships between patients and clinicians or other staff (radiology technicians) can produce solutions that work, such as assisting with position during mammography and for complete physical examinations.…”
Section: Discussionmentioning
confidence: 99%
“…33 Interviews with women with disabilities who had developed early-stage breast cancer found that they frequently confronted physical barriers to care, such as inaccessible examining tables, weight scales, infusion chairs, mammography machines, and radiology equipment. 35,36 For example, a woman who is paraplegic reported that the cancer clinic at a major academic medical center she was referred to did not have a weight scale that was accessible by wheelchair. A woman's weight determines certain chemotherapy dosages.…”
Section: Lifestyle Modificationmentioning
confidence: 98%